A Systematic Review of Change Control in Construction Projects: Causes, Impacts, and Challenges - Apriani, Widya; Latief, Yusuf; Riantini, Leni Sagita (Avenew Indonesia, 2026)
Construction projects experience frequent changes that significantly impact time performance. Existing change control systems remain fragmented and lack integration with digital technologies. Throughout the construction project lifecycle, dynamically occurring changes require structured and easily accessible information through the implementation of effective Change Management practices. Change control becomes a crucial element in project management to minimize delays, cost overruns, and conflicts. This study aims to identify critical gaps in current change control practices and propose on change management in construction projects, focusing on the comparison of best practice approaches, industry strategies, as well as opportunities for the development of new methods. Method: A systematic literature review (SLR) was conducted using the PRISMA approach. A total of 790 articles were initially identified, and 121 relevant studies were selected after screening. The findings indicate the existence of various change management systems, but there is no approach that comprehensively integrates knowledge, Work Breakdown Structure (WBS)-based change management, and Building Information Modeling (BIM) technology in one integrated framework. This research informs the development of an evolving change management system in construction project management. The contribution of this research is to provide new insights for academics and practitioners on the importance of technology integration and innovative strategies in construction project change management.